Life threatening hyperkalaemia with diarrhoea during ACE inhibition. Issue 2 (20th January 2005) - McGuigan, J; Robertson, S; Isles, C
Abstract : A 67 year old woman developed acute renal failure with serum potassium 9.4 mmol/l requiring emergency dialysis after seven days of diarrhoea while taking an ACE inhibitor for vascular disease. Review of the literature, the British National Formulary, and the patient information leaflets for each of the 11 ACE inhibitors currently marketed in the UK suggests that this potentially life threatening complication of ACE inhibition is not yet widely recognised.